Are outcome measures in allergic diseases relevant for the WHO's International Classification of Diseases in allergology?. Issue 3 (June 2019) - Tanno, Luciana Kase; Demoly, Pascal
Abstract : Purpose of review: To review and understand the impact of the outcome measures of allergic and hypersensitivity conditions for the WHO's International Classification of Diseases (ICD) and its impact in the management of anaphylaxis and identify potential strategies to improve patients' care and prevention. Recent findings: The pioneer chapter addressed to allergic and hypersensitivity conditions in the 11th version of the WHO's ICD is the result of the evidence-based academic technical actions consistently following of collaborations of the allergy community and integrated international initiatives in order to reach quality outcomes measures of allergies worldwide. Summary: Allergic and hypersensitivity conditions are increasing worldwide, however, they have never been well represented in the international classification systems, such as the ICD. The ALLERGY in ICD-11 initiative has been launched in 2012 in order to gather a better representation of these conditions in the ICD-11. As a result of the evidence-based academic technical actions acknowledged by the Joint Allergy Academies and the WHO, the pioneer chapter Allergy and hypersensitivity conditions has been constructed. This framework can be considered a milestone in the history of the allergy specialty. More reliable, accurate and comparable epidemiological data will be able to provide a big picture of these conditions and will support improvements in many levels of the health system. As knowledge derived from populations is key information for more realistic decision-making, the construction of the new section addressed to allergic and hypersensitivity conditions in the ICD-11 will allow the collection of more accurate epidemiological data to support quality management of patients, and better facilitate healthcare planning to implement public health measures to prevent and reduce the morbidity and mortality attributable to these conditions.